The Influence of Education and Depression on Autonomy of Women with Chronic Pelvic Pain: A Cross-sectional Study - Hermes de Freitas Barbosa; Antonio Alberto Nogueira; Júlio César Rosa e Silva; Omero Benedicto Poli Neto; Francisco José Candido dos Reis (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Objective Patient autonomy has great importance for a valid informed consent in clinical practice. Our objectives were to quantify thedomains of patient autonomy and to evaluate the variables that can affect patient autonomy in women with chronic pelvic pain. Methods This study is a cross sectional survey performed in a tertiary care University Hospital. Fifty-two consecutive women scheduled for laparoscopic management of chronic pelvic were included. Three major components of autonomy (competence, information or freedom) were evaluated using a Likert scale with 24 validated affirmatives. Results Competence scores (0.85 vs 0.92; p = 0.006) and information scores (0.90 vs 0.93; p = 0.02) were low for women with less than eight years of school attendance. Information scores were low in the presence of anxiety (0.91 vs 0.93; p = 0.05) or depression (0.90 vs 0.93; p = 0.01). Conclusions Our data show that systematic evaluation of patient autonomy can provide clinical relevant information in gynecology. Low educational level, anxiety and depression might reduce the patient autonomy in women with chronic pelvic pain.